Thyroid and Lipid Profile Dysfunction among Obese versus Non-Obese Individuals: Obesity and Thyroid Lipid Profile Dysfunction - Rizwan, Rizwan; Zafar, Adeel; Bashir, Sibgha; Abideen, Zen-Ul; Ejaz, Maryam; Zahid, Natasha; Haque, Mazhar Ul (Pakistan Journal of Health Sciences, 2024)
Obesity, a complex disorder influenced by both genetic and environmental factors, manifests through intricate interactions. Objective: To assess thyroid function tests and serum lipid profiles in obese and non-obese individuals. Methods: This cross sectional observational study was conducted over six months from July to December 2023 at the medical outpatient department of Shahida Islam Medical College, after obtaining ethical approval (IRB Ref no. SIMC/H.R./7314/23, dated May 1, 2023). A sample size of 200 was calculated, divided equally into obese (BMI > 30 kg/m²) and non-obese (BMI < 25 kg/m²) groups. Data were analyzed using SPSS version 23.0, employing chi-square tests for significance (p < 0.05). Results: Each group comprised 100 participants, with mean ages of 42.49 ± 9.0 years for the obese and 43.83 ± 6.2 years for the non-obese group. Females constituted 62% of the obese and 51% of the non-obese group. Mean BMI was 35.8 kg/m² and 26.6 kg/m² in the obese and non-obese groups, respectively. Obese individuals exhibited higher mean total cholesterol (173 ± 40.77 mg/dl vs. 134 ± 29.62 mg/dl, p = 0.05) and significant differences in HDL, LDL, triglycerides, TSH, T3, and T4 levels (p < 0.05). Conclusions: Obesity is associated with adverse thyroid and lipid profiles, with a higher prevalence among females. These findings underscore the importance of addressing these metabolic factors in obesity management.